KETERKAITAN ANTARA AUDITOR SWITCHING DENGAN FINANCIAL DISTRESS, AUDIT FEE, DAN AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR - Fatkhatul Ngulya; Yulida Army Nurcahya (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
Auditor switching is an event where the company changes its cooperation with the auditor and the Public Accounting Firm (KAP). Auditor switching can be done either mandatory or voluntary. Voluntary auditor switching can be caused by several factors such as financial distress, audit fees, and audit delay. Accounting phenomena that have occurred, such as the Enron and KAP Arthur Anderson cases, the Waste Management Inc case, the Satyam case in India and the PT Great River International, Tbk. case, prove the need for auditor independence in carrying out audit work in a company. One way that can be done to maintain auditor independence is to conduct auditor switching, so that the cooperation that exists between the auditor and the company is maintained properly. This research is a qualitative research where the researcher uses the literature study method. This literature study was conducted by researchers referring to previous studies to further analyze the effect of variables such as financial distress, audit fees, and audit delay on auditor switching in manufacturing companies. According to the results of literature studies that have been carried out by researchers in previous studies, it can be concluded that the financial distress variable has no effect on the occurrence of auditor switching, while the audit fee and audit delay variables have implications for the occurrence of auditor switching in manufacturing companies.